The isolation, bioactivity, and synthesis of natural products from Litsea verticillate with anti-HIV activities - Yan, Jia-Lei; Nan, Huiru; Fang, Xiaoyu; Long, Xiong-En; Jiang, Yu; Liu, Junyang (Frontiers in Pharmacology, 2024)
Natural products isolated from Litsea verticillata have attracted considerable attention from the chemical community due to their unique structures and promising anti-HIV activities. Recent progresses in the isolation and bioactivity studies for these natural molecules were summarized comprehensively. From the 23 previously uncharacterized compounds isolated from the plant Litsea verticillata, litseaverticillol B demonstrated the most potent anti-HIV activity in vitro, with IC50 ranging from 2 to 3 μg/mL. Meanwhile, litseaverticillol E displayed the highest selectivity index (SI = 3.1), indicating a favorable balance between antiviral potency and cellular toxicity. The plausible biosynthetic pathways and the total synthetic approaches for the representative members (litseaverticillols) were introduced in detail.